Definition of Internal Mammary Node Target Volume Based on the Position of the Internal Mammary Sentinel Lymph Nodes Presented on SPECT/CT Fusion Images - Wang, Xue; Wang, Wei; Li, Jian-Bin; Huo, Zong-Wei; Xu, Min; Qiu, Peng-Fei; Zhang, Ying-Jie; Li, Feng-Xiang; Wang, Jin-Zhi (Frontiers in Oncology, 2020)
Purpose: Mapping the distribution of internal mammary sentinel lymph nodes (IM-SLNs) presented on single photon emission computed tomography in conjunction with computed tomography (SPECT/CT) images to explore the value of IM-SLN to guide tailored clinical target volume (CTV) delineation of postoperative prophylactic IMNI. Materials and methods: Ninety-seven patients who underwent preoperative lymphoscintigraphy by SPECT/CT and had imaging of IM-SLN were selected in this study. The imaging IM-SLNs on SPECT/CT of eligible patients were projected onto corresponding anatomical positions of a representative axial CT image. The IMN CTVs were delineated on the representative axial CT images according to the Radiation Therapy Oncology Group (RTOG) and Danish Breast Cancer Cooperative Group (DBCG) guideline, and defined as CTVRTOG and CTVDBCG. The location of the IM-SLNs was compared with the RTOG and DBCG guidelines of IMN target volume delineations, respectively. The intercostal space distribution of IM-SLNs was recorded. The distances from the CTVRTOG and CTVDBCG to the IM-SLNs were measured, respectively. Results: The total number of imaging IM-SLNs was 136. IM-SLNs were mostly found in the first intercostal space (40.4%), with 30.2, 24.3, 4.4, and 0.7% of IM-SLNs in the second, third, fourth, and fifth intercostal space, respectively. The average distance from the edge of the CTVRTOG and the edge of CTVDBCG to the central points of the IM-SLNs was 4.10 mm (SD, 3.3 mm) and 1.60 mm (SD, 2.6 mm), respectively (t = 16.640, P = 0.000). The average distance from the edge of CTVRTOG and the edge of CTVDBCG to the lateral border IM-SLN was 6.40 mm (SD, 3.5 mm) and 3.34 mm (SD, 3.3 mm), respectively (t = 19.815, P = 0.000). Only 18.4% of IM-SLN central points were included in the CTVRTOG, and 60.3% of IM-SLN central points were included in the CTVDBCG. When covering 90 and 100% of the IM-SLN center points, the CTVRTOG needs to expand 8 and 15 mm, respectively, and the CTVDBCG needs to expand 5 and 13 mm, respectively. Conclusion: Neither the RTOG nor DBCG consensus guideline about the delineation of IMN CTV was sufficient to cover 90% of IM-SLNs. For 90% coverage of IM-SLN central points, CTVRTOG needed to be expanded by 8 mm, and CTVDBCG needed to be expanded by 5 mm.